1982
DOI: 10.1111/j.1600-0528.1982.tb00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of permanent tooth emergence in a Southeastern Dominican schoolchildren population sample

Abstract: The purpose of this study was to establish the mean timing of permanent tooth emergence in a low to middle socioeconomic level schoolchildren population sample from the Southeastern part of the Dominican Republic. A total of 900 children (15.6% of the 5-14-year-old schoolchildren from this city) were studied. Girls were relatively advanced in their emergence times except for the canine and second premolar in the maxilla and the first premolar in the mandible. The mean emergence times were, in general, relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The sequence of eruption in this study was similar to that reported in other studies done in Gambia, 13 Australia, 17 China, 7 Japan, 35 Kenyans of Asian origin, 36 and Indian studies from Chennai and Lahore, 37 Chandigarh, 38 and Delhi. 39 On comparison with the earlier studies done on children from Tanzania, 1 Iran, 2 Pima India, 11 New York, 12 West Africa (Gambia), 13 Japan, 14 Danish, 15 Australia, 17 French, 18 Kelatan (NorthEastern Malaysia), 19 Izmir (Turkey), 20 Malaysia, 21 Flemish, 22 Dominican Republic, 25 Athens (Greece), 28 Eskimo, 40 Finn, 41 South India, 10 Nigeria, 42 and Romania, 43 there was overall delay in the eruption of permanent teeth. When compared with the age of eruption of permanent canine and premolar teeth in Kerman Province children, 24 there was early eruption of these teeth in the present study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The sequence of eruption in this study was similar to that reported in other studies done in Gambia, 13 Australia, 17 China, 7 Japan, 35 Kenyans of Asian origin, 36 and Indian studies from Chennai and Lahore, 37 Chandigarh, 38 and Delhi. 39 On comparison with the earlier studies done on children from Tanzania, 1 Iran, 2 Pima India, 11 New York, 12 West Africa (Gambia), 13 Japan, 14 Danish, 15 Australia, 17 French, 18 Kelatan (NorthEastern Malaysia), 19 Izmir (Turkey), 20 Malaysia, 21 Flemish, 22 Dominican Republic, 25 Athens (Greece), 28 Eskimo, 40 Finn, 41 South India, 10 Nigeria, 42 and Romania, 43 there was overall delay in the eruption of permanent teeth. When compared with the age of eruption of permanent canine and premolar teeth in Kerman Province children, 24 there was early eruption of these teeth in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Eruption of all the remaining teeth was earlier in boys. Garcia-Godoy et al 25 reported early eruption of permanent teeth in girls with exception of canine and second premolar in maxilla and first premolar in mandible in South Eastern Dominican children. In a study done in North Ireland, 26 earlier eruption of permanent teeth was found in girls with exception of permanent second molar eruption in both the arches.…”
Section: Discussionmentioning
confidence: 99%
“…In Scandinavian children, emergence occurred at approximately the same age or slightly later (1–4) than in Flemish children (5). In the Dominican Republic (6) and Japan (7), however, the emergence of most permanent teeth was observed at an earlier age. Differences in study design and research methodology may explain the observed differences.…”
Section: Comparison Of Mean Permanent Tooth Emergence Ages For Girlsmentioning
confidence: 99%
“…Differences in study design and research methodology may explain the observed differences. A genetic influence on the timing of tooth emergence has also been suggested (6, 8, 9). The impact of climate, nutrition and socio‐economic factors on tooth emergence is still under debate (10–12).…”
Section: Comparison Of Mean Permanent Tooth Emergence Ages For Girlsmentioning
confidence: 99%
“…The most significant post-1972 improvement on the formation and eruption sequence was published by Ubelaker (1978), who expanded the results of several earlier studies and compiled them into charts. From a forensic standpoint, it is imperative to remember that dental growth is extremely sensitive to sex and populational differences (e.g., Garn et al, 1973;Demirjian, 1978;Garcia-Godoy et al, 1982).In the adult, morphological variation is much more subtle and the sequence of chronological developments is not as orderly. Most studies on adult aging techniques can be traced to Todd's work in the 1920s on the pubic symphysis and cranial sutures (e.g., Todd, 1920;Todd and Lyon, 1924) and much later to McKern and Stewart in 1957.…”
mentioning
confidence: 98%